Kahoot as an Assessment Tools: Students' Perception of Game-based Learning Platform - Iman, Nurul; Ramli, Munasprianto; Saridewi, Nanda (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to determine students' perception of game-based learning platform as a learning evaluation medium. The approach used in this research is descriptive quantitative, and qualitative—the instrument used in the form of a questionnaire containing 22 questions and interviews. The research was conducted in two analytical chemistry classes at a public university in Indonesia. Researchers used Kahoot every two weeks over four months as a tool for formative assessment. Three students from each class were interviewed to explore their experiences and perceptions of Kahoot. Questionnaire data were processed using descriptive statistics, while data from interviews were analyzed using thematic analysis. The findings show that chemistry education students' perception of game-based learning platform as a learning evaluation medium is quite good. Students also perceived that Kahoot provided a challenge in learning. Kahoot is also a fun and exciting assessment medium for students. In addition, students feel that their learning motivation has increased in preparing the material to be tested, so direct feedback from Kahoot is very effective in correcting mistakes.